Advancements and challenges in enhancing salt hydrate phase change materials for building energy storage: Optimization methodologies and mechanisms - Yang Haibin; Zou Yang; Cui Hongzhi (National Science Open)
The application of phase change materials (PCMs) into buildings is a prospective method for mitigating energy consumption in the construction sector. Among the diverse PCM options, salt hydrate PCMs stand out for their superior thermal storage densities, adaptable operating temperature ranges, and cost-effectiveness, rendering them highly attractive for practical engineering applications. However, the utilization of salt hydrates has encountered obstacles, including pronounced supercooling, severe phase separation, and insufficient thermal conductivity, limiting their efficacy in energy storage solutions. In response to these challenges and in pursuit of rendering salt hydrates viable for building energy storage systems, substantial research has been conducted in recent years. This paper offers a comprehensive overview of the strategies devised to address the challenges associated with salt hydrate PCMs, and it also elucidates the corresponding optimization methodologies and bolstering mechanisms, providing a valuable resource for researchers in this field.